The detection of isochromosome i(12p) in malignant germ cell tumours and tumours with somatic malignant transformation by the use of quantitative real‐time polymerase chain reaction. Issue 4 (21st November 2020) - Fichtner, Alexander; Richter, Annika; Filmar, Simon; Gaisa, Nadine T; Schweyer, Stefan; Reis, Henning; Nettersheim, Daniel; Oing, Christoph; Gayer, Fabian A; Leha, Andreas; Küffer, Stefan; Ströbel, Philipp; et al.
Abstract : Aims: Malignant germ cell tumours (GCTs) of the testis are rare neoplasms, but the most common solid malignancies in young men. World Health Organization guidelines divide GCTs into five types, for which numerous immunohistochemical markers allow exact histological subtyping in the majority of cases. In contrast, a germ cell origin is often hard to prove in metastatic GCTs that have developed so‐called somatic malignant transformation. A high percentage, up to 89%, of GCTs are characterised by the appearance of isochromosome 12p [i(12p)]. Fluorescence in‐situ hybridisation has been the most common diagnostic method for the detection of i(12p) so far, but has the disadvantages of being time‐consuming, demanding, and not being a stand‐alone method. The aim of the present study was to establish a quantitative real‐time polymerase chain reaction assay as an independent method for detecting i(12p) and regional amplifications of the short arm of chromosome 12 by using DNA extracted from formalin‐fixed paraffin‐embedded tissue. Methods and results: A cut‐off value to distinguish between the presence and absence of i(12p) was established in a control set consisting of 36 tumour‐free samples. In a training set of 149 GCT samples, i(12p) was detectable in 133 tumours (89%), but not in 16 tumours (11%). In a test set containing 27 primary and metastatic GCTs, all 16 tumours with metastatic spread and/or somatic malignant transformation were successfully identified by the detection of i(12p). Conclusion: In summary, the qPCR assay presented here can help to identify, further characterise and assign a large proportion of histologically inconclusive malignancies to a GCT origin.